Dividing the Archaeal Way: The Ancient Cdv Cell-Division Machinery - Caspi, Yaron; Dekker, Cees (Frontiers in Microbiology, 2018)
Cell division in most prokaryotes is mediated by the well-studied fts genes, with FtsZ as the principal player. In many archaeal species, however, division is orchestrated differently. The Crenarchaeota phylum of archaea features the action of the three proteins, CdvABC. This Cdv system is a unique and less-well-studied division mechanism that merits closer inspection. In vivo, the three Cdv proteins form a composite band that contracts concomitantly with the septum formation. Of the three Cdv proteins, CdvA is the first to be recruited to the division site, while CdvB and CdvC are thought to participate in the active part of the Cdv division machinery. Interestingly, CdvB shares homology with a family of proteins from the eukaryotic ESCRT-III complex, and CdvC is a homologue of the eukaryotic Vps4 complex. These two eukaryotic complexes are key factors in the endosomal sorting complex required for transport (ESCRT) pathway, which is responsible for various budding processes in eukaryotic cells and which participates in the final stages of division in Metazoa. There, ESCRT-III forms a contractile machinery that actively cuts the membrane, whereas Vps4, which is an ATPase, is necessary for the turnover of the ESCRT membrane-abscission polymers. In contrast to CdvB and CdvC, CdvA is unique to the archaeal Crenarchaeota and Thaumarchaeota phyla. The Crenarchaeota division mechanism has often been suggested to represent a simplified version of the ESCRT division machinery thus providing a model system to study the evolution and mechanism of cell division in higher organisms. However, there are still many open questions regarding this parallelism and the division mechanism of Crenarchaeota. Here, we review the existing data on the role of the Cdv proteins in the division process of Crenarchaeota as well as concisely review the ESCRT system in eukaryotes. We survey the similarities and differences between the division and abscission mechanisms in the two cases. We suggest that the Cdv system functions differently in archaea than ESCRT does in eukaryotes, and that, unlike the eukaryotic case, the Cdv system’s main function may be related to surplus membrane invagination and cell-wall synthesis.